A Linear-Correction Algorithm for Quasi-Synchronous DFT. (27th December 2018) - Fu, Zhongjun; Wang, Jianyu; Ou, Yun; Zhou, Genyuan; Zhao, Xiaorong
Abstract : Spectral leakage in the harmonic measured by quasi-synchronous DFT (QSDFT) is mainly due to short-range leakage caused by deviation in the signal frequency. By analysing the short-range-leakage characteristic of QSDFT, a linear-correction algorithm (LCQS) for QSDFT's harmonic-analysis results is proposed. LCQS contains two linear-correction equations: an amplitude-correction equation and an initial-phase-angle-correction equation. The former is constructed by the least-squares method, whereas the latter is generated based on the linear error characteristic of the QSDFT harmonic phase. Simulation and experimental results indicate that this proposed algorithm can efficiently increase the accuracy of the harmonic parameters over a wide frequency range by minimizing the short-range spectral leakage.